Kajian Teknis dan Ekonomis dalam Merencanakan Penggantian Alat Angkut pada Pengupasan Overburden Penambangan Batubara PT Citra Mitra Sehati Site Job PT Cakra Bumi Pertiwi di Kecamatan Ulok Kupai, Kabupaten Bengkulu Utara, Provinsi Bengkulu - Fattah Aulia Rachman; Zaenal; Iswandaru (Bandung Conference Series: Mining Engineering, 2023)
Abstract. PT Citra Mitra Sehati is one of the companies engaged in mining using the Open Mining. The location of this company is in Ulok Kupai District, Notrh Bengkulu Regency, Bengkulu Province. Mining activities use 1 Dossan Dx 500 Excavator and 10 Dumptruck Tranporting Hino 700. The age of this mechanical tool has almost reached its service life and frequent breakdowns occur, resulting in decreased tool performance and greater operating costs. This of course affects the productivity and production which is decreasing. Therefore, it is necessary to plan to replace the tool or not. The purpose of this study is to determine the comparison of the production of old equipment and new equipment, and the economic comparison includes operating costs, ownership costs, Present Worth Cost and Production Unit Cost values. The research method is taking primary data and also secondary data. The primary data in this research are working time, excavator bucket material volume, circulation time, resistance time, in situ density testing, density loose testing, and haul road data. Secondary data in this study are equipment specifications, fuel prices, lubricating oil prices, filter prices, tool life, trade in value, depreciation, tax and insurance, inflation and interest rates. From the primary and secondary data, the results of the production value, operating costs, ownership costs, Present Worth Cost, and Production Unit Costs for old and new tools are obtained. Based on the results of technical and economic studies, the old transporting production with production of 761.776,63 BCM/year and new transporting production of 990.964,80 BCM/year. Based on the results of an economic study, the Present Worth Cost of the old equipment was IDR 9,132,362,361.05 and the new equipment was IDR 18,478,081,688.32. The cost of calculating the old transporting of the cost of Production Unit Cost IDR 2.997,06 /BCM and new transporting of IDR 2.071,84 BCM. Based on technical and economic studies for excavating and transporting equipment needs to be replaced because the productivity of new tools is greater and operating costs are more efficient than old tools, from the results of Unit Cost Production for excavating and transporting new tools is more efficient than old tools, as well as long-term investment if buying new tools. Abstrak. PT Citra Mitra Sehati merupakan salah satu perusahaan yang bergerak di bidang pertambangan dengan menggunakan Sistem Tambang Terbuka. Lokasi perusahaan ini terletak di Kecamatan Ulok Kupai, Kabupaten Bengkulu Utara, Provinsi Bengkulu. Kegiatan penambangan mengunakan 1 alat gali-muat Excavator Dossan Dx 500 dan 10 alat angkut Dump Truck Hino 700. Umur alat mekanis ini hampir mencapai umur pemakaian dan sering terjadi kerusakan, sehingga mengalami penurunan kinerja alat dan biaya operasinya semakin besar. Hal ini tentunya mempengaruhi produktivitas dan produksinya yang semakin menurun. Oleh karena itu perlu merencanakan penggantian alat atau tidak. Adapun tujuan penelitian ini adalah mengetahui perbandingan produksi alat lama dan alat baru, serta perbandingan secara ekonomis meliputi biaya operasi, biaya kepemilikan, nilai Present Worth Cost dan nilai Production Unit Cost. Data primer pada penelitian ini yaitu waktu kerja, volume material bucket excavator, waktu edar, waktu hambatan, pengujian density insitu, pengujian density loose, dan data jalan angkut. Data sekunder pada penelitian ini yaitu spesifikasi alat, harga bahan bakar, harga minyak pelumas, harga filter, umur alat, nilai trade in value, depresiasi, tax and insurance, inflasi, dan tingkat suku bunga. Dari data primer dan sekunder dihitung sehingga mendapatkan hasil nilai produksi, biaya operasi, biaya kepemilikan, Present Worth Cost dan Production Unit Cost untuk alat lama dan alat baru. Berdasarkan hasil kajian teknis dan ekonomis alat angkut lama produksi dengan produksi sebesar 761.776,63 BCM/tahun dan alat angkut baru produksi sebesar 990.964,80 BCM/tahun. Berdasarkan hasil kajian ekonomi didapatkan hasil Present Worth Cost alat lama Rp 9.132.362.361,05 dan alat baru sebesar Rp 18.478.081.688,32. Perhitungan biaya Production Unit Cost untuk alat angkut lama biaya Production Unit Cost Rp 2.998,03 /BCM dan alat angkut baru sebesar Rp 2.071,80 /BCM. Berdasarkan kajian teknis dan ekonomis untuk alat angkut lama perlu diganti karena produktivitas alat baru lebih besar dan biaya operasi lebih hemat dibandingkan alat lama, dari hasil Unit Cost Production untuk alat angkut baru lebih hemat dibandingkan alat lama, serta investasi jangka panjang jika membeli alat baru.